Blaming it on NATO? Framing the role of NATO in the full-scale Russian invasion of Ukraine on Twitter - Kobilke, Lara; Kulichkina, Aytalina; Baghumyan, Ani; Pipal, Christian (Frontiers in Political Science, 2023)
Introduction Since social media has become a significant tool for conflict communication amid the full-scale Russian invasion of Ukraine, researchers have grown more interested in the digital content citizens are exposed to. Methods To further investigate the role of social media in the ongoing invasion, we conducted a manual content analysis to examine tweets in English, Russian, and German that explicitly mentioned NATO in the context of the full-scale invasion during February to May 2022. Our analysis explored how these language-specific Twitter communities framed NATO's role in the conflict. Results We found that English-speaking tweeters were more likely to hold NATO responsible for finding a solution and least likely to blame NATO for the war compared to German and Russian speakers. We also observed that the Russian-speaking Twitter community exhibits a comparatively lower tendency to hold NATO accountable for the ongoing war as compared to their German-speaking counterparts, and they are also notably the least likely to expect NATO to bring an end to the war. Finally, English-speaking Twitter users who attribute blame to NATO for the ongoing war tend to adhere to a preconceived notion, rather than arriving at an interpretation based on the situation at hand. This is in contrast to the Russian-speaking community, where the opposite is true. German-speaking users fall somewhere in between these two perspectives. Discussion Our research contributes to the literature by providing a novel integration of conceptual and methodological perspectives on the framing and stance-taking of social media users during wartime, addressing known research gaps in the comparative analysis of these discussions, i.e., adding “non-English” perspectives. It also highlights the importance of cultural and linguistic sensitivity when addressing responsibility in armed conflicts and the need to consider the diverse perspectives derived from divergent problem definitions and evaluative standards.